A method for preparing a hollow composite carbon sphere

CN118723969BActive Publication Date: 2026-10-27郑州坚峰复合材料有限公司
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410711712.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-03
Publication Date
2026-10-27
Estimated Expiration
2044-06-03

AI Technical Summary

Technical Problem

[0004]目前,现有技术所制备的空心复合碳球存在团聚、壁厚不均匀等问题,因此,开发一种高球形度的空心复合碳球的制备方法具有十分重要的意义

Benefits of technology

[0026]本发明以高效的方式进行反应,即使混合溶液B分批次加入混合溶液A中,避免酚醛树脂微球在合成过程中自身发生黏连,同时使生成的酚醛树脂微球均匀包覆在空心玻璃微珠表面,从而得到球形度高的空心复合酚醛树脂球,经烧结碳化后得到球形度高的空心复合碳球;通过调整合成的酚醛树脂的量可以调整空心玻璃微珠表面碳层厚度,从而调整空心复合碳球的尺寸,更有利于实际应用和工业化生产。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118723969B_ABST
    Figure CN118723969B_ABST
Patent Text Reader

Abstract

The present application belongs to the field of special structure carbon material, and discloses a preparation method of hollow composite carbon spheres. Hollow glass microspheres are used as hollow templates, phenols and aldehydes are used as raw materials, and phenolic resin microspheres are in-situ synthesized at normal temperature under the action of a catalyst and a dispersant, so that the phenolic resin microspheres are coated on the surface of the hollow glass microspheres to form hollow composite phenolic resin spheres, and then the hollow composite phenolic resin spheres are carbonized to form hollow composite carbon spheres. The present application does not need to perform preliminary treatment on the microspheres, and does not need to remove the templates through an additional step, and the prepared hollow composite carbon spheres have high sphericity, which is more conducive to practical application and industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of special structure carbon materials, specifically relating to a method for preparing hollow composite carbon spheres. Background Technology

[0002] Hollow carbon spheres are lightweight fillers with a cavity structure and low density, and are widely used in catalysts, adsorbents, buoyancy materials and other fields.

[0003] Existing methods for preparing porous hollow carbon spheres have several shortcomings. For example, the preparation of the silica template and the process of coating the spheres with organic matter are carried out in separate steps. Additional washing and separation processes are required to purify the template. Before coating, the template needs to be sonicated to ensure uniform dispersion. During coating, surfactants and reactants need to be added in multiple steps, which is cumbersome and requires extremely precise control. After coating, since the silica template is a solid sphere, acid washing is necessary to remove the template.

[0004] Currently, hollow composite carbon spheres prepared by existing technologies suffer from problems such as agglomeration and uneven wall thickness. Therefore, developing a method for preparing hollow composite carbon spheres with high sphericity is of great significance. Summary of the Invention

[0005] This invention proposes a method for preparing hollow composite carbon spheres by in-situ coating of phenolic resin-based carbon materials onto the surface of hollow glass microspheres. This patented method eliminates the need for pretreatment of the microspheres and removal of the template, and the prepared hollow composite carbon spheres exhibit high sphericity, making them more suitable for practical applications and industrial production.

[0006] The purpose of this invention is to provide a hollow composite carbon sphere with a simple reaction process, environmental friendliness, and high sphericity, as well as its preparation method.

[0007] The technical solution adopted in this invention is a method for preparing hollow composite carbon spheres, which is implemented according to the following steps:

[0008] Mix the phenol source, catalyst, hollow glass microspheres and water to prepare mixed solution A; mix formaldehyde and dispersant to prepare mixed solution B.

[0009] Divide the mixed solution B into at least two portions. Add one portion of mixed solution B to mixed solution A each time and mix and stir until mixed solution B and mixed solution A are completely mixed to obtain mixed solution C.

[0010] The mixed solution C was dried to obtain hollow composite phenolic resin spheres, which consist of hollow glass microspheres and phenolic resin coating the hollow glass microspheres.

[0011] Hollow composite phenolic resin spheres are sintered to obtain hollow composite carbon spheres, which include hollow glass microspheres and a carbon layer coating the hollow glass microspheres.

[0012] Thus, by using hollow glass microspheres as templates to in-situ coat phenolic resin microspheres onto the template surface, hollow composite carbon spheres can be prepared without the need for additional template removal steps. The introduction of a dispersant ensures the synthesized hollow composite carbon spheres exhibit good stability, high monodispersity, and prevents them from agglomerating. Furthermore, by controlling the synthesis method of mixed solution C—adding a portion of mixed solution B to mixed solution A before adding the remaining solution B—the synthesized phenolic resin microspheres grow in situ on the surface of the hollow glass microspheres after each addition. Slow mixing allows the prepared phenolic resin microspheres to uniformly and densely coat the surface of the hollow glass microspheres, preventing the microspheres from agglomerating.

[0013] The invention is further characterized by:

[0014] In some embodiments, the mixed solution B is divided into at least two portions, and one portion of mixed solution B is added to mixed solution A each time and mixed and stirred until mixed solution B and mixed solution A are completely mixed to obtain mixed solution C. The mixing and stirring temperature is 15°C to 35°C and the stirring time is 0.5h to 1h each time.

[0015] Preferably, the mixed solution B is divided into two parts, B1 and B2, with a mass fraction of (1 / 5 to 1 / 2):(4 / 5 to 1 / 2). First, B1 is added to the mixed solution A and mixed and stirred. Then, B2 is divided into 1 to 10 parts, and one part is added to the mixed solution A each time and mixed and stirred until the mixed solution B and mixed solution A are completely mixed to obtain mixed solution C.

[0016] Ideally, the mixed solution B2 should be divided into 2 to 6 equal parts.

[0017] Thus, when mixed solution B is first added to mixed solution A, slow stirring allows the phenolic resin microspheres generated from the phenol source and formaldehyde to coat the surface of the hollow glass microspheres. The microspheres are tightly packed together, forming a dense layer of phenolic resin microspheres. Each subsequent addition of mixed solution B to mixed solution A results in a uniform coating of phenolic resin microspheres on the surface of the hollow composite phenolic resin spheres, forming a multi-layered structure. This process of adding small amounts multiple times and slow mixing ensures that the newly generated phenolic resin microspheres grow on the surface of the hollow composite phenolic resin spheres without agglomeration, resulting in hollow composite phenolic resin spheres with high sphericity and uniform wall thickness. Furthermore, by controlling the amount of synthesized phenolic resin, the wall thickness can be further controlled, resulting in hollow composite resin spheres with controllable dimensions.

[0018] In some embodiments, the mass ratio of phenol source, catalyst, hollow glass microspheres, water, formaldehyde and dispersant is (8-30):(6-20):(10-30):(100-200):(3-18):1.

[0019] Thus, by adjusting the amount of synthesized phenolic resin, the thickness of the carbon layer on the surface of the hollow glass microspheres can be adjusted, thereby adjusting the size of the hollow composite carbon spheres.

[0020] In some embodiments, the phenol source is selected from one or more of p-aminophenol, m-aminophenol, o-aminophenol, resorcinol, catechol, hydroquinone, and phloroglucinol.

[0021] In some embodiments, the dispersant is selected from one or more of Tween 80, Tween 60, polyvinyl alcohol, polypyrrolidone, polyethylene glycol, sodium dodecyl sulfonate, sodium dodecyl sulfate, hexadecyl ammonium bromide, OP-30, and triblock copolymer F127.

[0022] In some embodiments, the catalyst is selected from one or more of ammonia, triethylamine, sodium hydroxide, potassium hydroxide, barium hydroxide, magnesium hydroxide, and sodium carbonate.

[0023] In some embodiments, the size of the hollow glass microspheres is 1–100 μm.

[0024] In some embodiments, hollow composite phenolic resin balls are sintered. The sintering process involves first heating to 180–250°C and holding for 0.5–1 hour, then heating to 400–800°C and holding for 1–2 hours.

[0025] Beneficial effects:

[0026] This invention employs a highly efficient reaction method, allowing mixed solution B to be added to mixed solution A in batches. This prevents the phenolic resin microspheres from sticking together during synthesis and ensures that the generated phenolic resin microspheres uniformly coat the surface of hollow glass microspheres, resulting in hollow composite phenolic resin spheres with high sphericity. After sintering and carbonization, hollow composite carbon spheres with high sphericity are obtained. By adjusting the amount of synthesized phenolic resin, the thickness of the carbon layer on the surface of the hollow glass microspheres can be adjusted, thereby adjusting the size of the hollow composite carbon spheres, which is more beneficial for practical applications and industrial production. Attached Figure Description

[0027] Figure 1 These are hollow glass microspheres coated with phenolic resin microspheres obtained using the preparation method of this invention.

[0028] Figure 2 This is a SEM image of a hollow composite carbon sphere with high sphericity obtained using the preparation method of this invention. Detailed Implementation

[0029] Example 1

[0030] S1: Weigh resorcinol, ammonia, hollow glass microspheres (D50 = 5 μm), water, formaldehyde, and hexadecyl ammonium bromide in a mass ratio of 19:13:20:150:11:1 respectively; mix the weighed resorcinol, ammonia, hollow glass microspheres, and water to prepare mixed solution A; mix formaldehyde and hexadecyl ammonium bromide to prepare mixed solution B;

[0031] S2: First, take 1 / 3 of the mixed solution B and mix it with mixed solution A at 25℃ for 0.8h. Then, add the remaining 2 / 3 of the mixed solution B in 3 batches, mixing and stirring at 25℃ for 0.8h after each addition, to obtain mixed solution C. Centrifuge, wash with water, and dry mixed solution C to obtain hollow composite phenolic resin balls. Heat the hollow composite phenolic resin balls in a tube furnace to 200℃ and hold for 0.8h, then heat to 600℃ and hold for 1.5h to obtain hollow composite carbon balls.

[0032] Example 2

[0033] S1: Weigh p-aminophenol, triethylamine, hollow glass microspheres (D50 = 5 μm), water, formaldehyde, and triblock copolymer F127 in a mass ratio of 30:20:30:1200:18:1 respectively; mix the weighed p-aminophenol, triethylamine, hollow glass microspheres, and water to prepare mixed solution A; mix formaldehyde and triblock copolymer F127 to prepare mixed solution B;

[0034] S2: First, take 1 / 3 of the mixed solution B and mix it with mixed solution A at 35℃ for 1 hour. Then, add the remaining 2 / 3 of the mixed solution B in 3 batches, mixing and stirring at 35℃ for 1 hour after each addition to obtain mixed solution C. Centrifuge, wash with water, and dry mixed solution C to obtain hollow composite phenolic resin balls. Heat the hollow composite phenolic resin balls in a tube furnace to 250℃ and hold for 1 hour, then heat to 800℃ and hold for 2 hours to obtain hollow composite carbon balls.

[0035] Example 3

[0036] S1: Weigh out phloroglucinol, sodium hydroxide, hollow glass microspheres, water, formaldehyde, and Tween 80 in a mass ratio of 8:6:10:100:3:1 respectively; mix the weighed phloroglucinol, sodium hydroxide, hollow glass microspheres, and water to prepare mixed solution A; mix formaldehyde and Tween 80 to prepare mixed solution B.

[0037] S2: First, take 1 / 3 of the mixed solution B and mix it with mixed solution A at 15℃ for 0.5h. Then, add the remaining 2 / 3 of the mixed solution B in 3 batches, mixing and stirring at 15℃ for 0.5h after each addition to obtain mixed solution C. Centrifuge, wash with water, and dry mixed solution C to obtain hollow composite phenolic resin balls. Heat the hollow composite phenolic resin balls in a tube furnace to 180℃ and hold for 0.5h, then heat to 400℃ and hold for 1h to obtain hollow composite carbon balls.

[0038] Example 4

[0039] S1: Weigh resorcinol, ammonia, hollow glass microspheres (D50 = 5 μm), water, formaldehyde, and hexadecyl ammonium bromide in a mass ratio of 19:13:20:150:11:1 respectively; mix the weighed resorcinol, ammonia, hollow glass microspheres, and water to prepare mixed solution A; mix formaldehyde and hexadecyl ammonium bromide to prepare mixed solution B;

[0040] S2: First, take 1 / 5 of the mixed solution B and mix it with mixed solution A at 25℃ for 0.8h. Then, add the remaining 4 / 5 of the mixed solution B in 5 batches, mixing and stirring at 25℃ for 0.8h after each addition to obtain mixed solution C. Centrifuge, wash with water, and dry mixed solution C to obtain hollow composite phenolic resin balls. Heat the hollow composite phenolic resin balls in a tube furnace to 200℃ and hold for 0.8h, then heat to 600℃ and hold for 1.5h to obtain hollow composite carbon balls.

[0041] Example 5

[0042] S1: Weigh resorcinol, ammonia, hollow glass microspheres (D50 = 5 μm), water, formaldehyde, and hexadecyl ammonium bromide in a mass ratio of 19:13:20:150:11:1 respectively; mix the weighed resorcinol, ammonia, hollow glass microspheres, and water to prepare mixed solution A; mix formaldehyde and hexadecyl ammonium bromide to prepare mixed solution B;

[0043] S2: First, take 1 / 2 part of mixed solution B and mix it with mixed solution A at 25℃ for 0.8h. Then, add the remaining 1 / 2 part of mixed solution B in two batches, mixing and stirring at 25℃ for 0.8h after each addition to obtain mixed solution C. Centrifuge, wash with water, and dry mixed solution C to obtain hollow composite phenolic resin balls. Heat the hollow composite phenolic resin balls in a tube furnace to 200℃ and hold for 0.8h, then heat to 600℃ and hold for 1.5h to obtain hollow composite carbon balls.

[0044] Example 6

[0045] S1: Weigh resorcinol, ammonia, hollow glass microspheres (D50 = 5 μm), water, formaldehyde, and hexadecyl ammonium bromide in a mass ratio of 19:13:20:150:11:1 respectively; mix the weighed resorcinol, ammonia, hollow glass microspheres, and water to prepare mixed solution A; mix formaldehyde and hexadecyl ammonium bromide to prepare mixed solution B;

[0046] S2: First, take half of the mixed solution B and mix it with mixed solution A at 25℃ and stir for 0.8h. Then, add the remaining half of the mixed solution and mix and stir at 25℃ for 0.8h to obtain mixed solution C. Centrifuge, wash with water, and dry mixed solution C to obtain hollow composite phenolic resin balls. Heat the hollow composite phenolic resin balls in a tube furnace to 200℃ and hold for 0.8h, then heat to 600℃ and hold for 1.5h to obtain hollow composite carbon balls.

[0047] Comparative Example 1

[0048] The difference from Example 1 is that:

[0049] The preparation method of mixed solution C is as follows: First, take 2 / 3 part of mixed solution B and mix it with mixed solution A at 25°C and stir for 0.8 h; then add the remaining 1 / 3 part of mixed solution B in 3 batches. The rest is the same as in Example 1.

[0050] Comparative Example 2

[0051] The difference from Example 1 is that:

[0052] The mixing method for mixed solution C is as follows: Take all of mixed solution B and mixed solution A, mix and stir at 25°C for 0.8 hours to obtain mixed solution C. All other steps are the same as in Example 1.

[0053] Test method: The wall thickness of the hollow composite carbon spheres in the TEM image was measured, and the standard deviation of the wall thickness was calculated.

[0054] (1) Take one hollow composite carbon sphere from each group of samples, and measure the wall thickness at 10 points on each hollow composite carbon sphere using the formula. Calculate the standard deviation of wall thickness for each group;

[0055] (2) Take 50 hollow composite carbon spheres from each sample group, and measure the wall thickness at one point on each of the 50 hollow composite carbon spheres in each group. Calculate the wall thickness using the formula... Calculate the standard deviation of wall thickness for each group;

[0056] (3) Calculate the equivalent diameter of the largest particle when the cumulative distribution is 50% in each particle size distribution curve.

[0057] Test results:

[0058]

[0059] Examples 1-3 adjusted the proportions of each component and used hollow glass microspheres of the same particle size, resulting in hollow composite carbon spheres with high sphericity and diameters that increased with the amount of raw materials added. Examples 4-5 adjusted the mixing method of mixed solution A and mixed solution B, changing the amount of phenolic resin generated in each mixing compared to Example 1. The standard deviation of the wall thickness and the equivalent diameter of the prepared hollow composite carbon spheres were slightly increased compared to Example 1. Example 6 reduced the number of times mixed solution B was added to mixed solution A. Because mixing and stirring occurred after each addition, a larger amount of phenolic resin microspheres were generated, which to some extent caused some of the phenolic resin microspheres to agglomerate, reducing the uniformity of the phenolic resin microsphere layer on the outer layer of the hollow glass microspheres. Therefore, the standard deviation of the wall thickness and the equivalent diameter of the prepared hollow composite carbon spheres were slightly increased compared to Example 1.

[0060] Compared with Example 1, Comparative Examples 1-2 used the same amount of resin coating. Comparative Examples 1-2 changed the way mixed solution A and mixed solution B were added, resulting in a poorer coating effect of the phenolic resin microspheres on the hollow glass microspheres, and the prepared hollow composite carbon spheres had uneven wall thickness and unstable dimensions.

[0061] Although the present invention has been described in detail with reference to preferred embodiments, it is not limited thereto. Various equivalent modifications or substitutions can be made to the embodiments of the present invention by those skilled in the art without departing from the spirit and essence of the invention, and such modifications or substitutions should all be within the scope of the present invention. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should also be covered within the protection scope of the present invention. Therefore, the protection scope of the present invention should be determined by the scope of the claims.

Claims

1. A method for preparing hollow composite carbon spheres, characterized in that, The specific steps are as follows: Mix the phenol source, catalyst, hollow glass microspheres, and water to prepare mixed solution A. Mix formaldehyde and dispersant to prepare mixed solution B. Divide mixed solution B into two parts, B1 and B2, with a mass fraction of (1 / 5~1 / 2):(4 / 5~1 / 2). First, add B1 to mixed solution A and mix and stir. Then, divide B2 into 1~10 equal parts and add them to mixed solution A and mix and stir until mixed solution B and mixed solution A are completely mixed to obtain mixed solution C. The mixed solution C is dried to obtain hollow composite phenolic resin balls, wherein the composite phenolic resin balls include hollow glass microspheres and phenolic resin coating the hollow glass microspheres; The hollow composite phenolic resin spheres are sintered to obtain hollow composite carbon spheres; The dispersant is selected from one or more of Tween 80, Tween 60, polyvinyl alcohol, polypyrrolidone, polyethylene glycol, sodium dodecyl sulfonate, sodium dodecyl sulfate, hexadecyl ammonium bromide, OP-30, and triblock copolymer F127; the catalyst of the hollow composite carbon spheres is selected from one or more of ammonia, triethylamine, sodium hydroxide, potassium hydroxide, barium hydroxide, and magnesium hydroxide.

2. The method for preparing hollow composite carbon spheres according to claim 1, characterized in that, Each time the mixture is mixed, the mixing temperature is 15℃~35℃ and the mixing time is 0.5h~1h.

3. The method for preparing hollow composite carbon spheres according to claim 2, characterized in that, After dividing mixed solution B2 into 2 to 6 equal parts, add mixed solution A and mix and stir.

4. The method for preparing hollow composite carbon spheres according to claim 1, characterized in that, The mass ratio of the phenol source, catalyst, hollow glass microspheres, water, formaldehyde and dispersant is (8~30):(6~20):(10~30):(100~200):(3~18):

1.

5. The method for preparing hollow composite carbon spheres according to claim 1, characterized in that, The phenol source is selected from one or more of p-aminophenol, m-aminophenol, o-aminophenol, resorcinol, catechol, hydroquinone, and phloroglucinol.

6. The method for preparing hollow composite carbon spheres according to claim 1, characterized in that, The hollow glass microspheres have a particle size of 1~100um.

7. The method for preparing hollow composite carbon spheres according to claim 1, characterized in that, The hollow composite phenolic resin balls are sintered. The sintering process involves first heating to 180~250℃ and holding for 0.5h~1h, then heating to 400~800℃ and holding for 1h~2h.

8. A hollow composite carbon sphere, characterized in that: The hollow composite carbon spheres are prepared by the method according to any one of claims 1-7, wherein the hollow composite carbon spheres comprise hollow glass microspheres and a carbon layer coating the hollow glass microspheres; The outer diameter of the carbon layer is 3-106 μm, the inner diameter is 1-100 μm, and the thickness of the carbon layer is 1-3 μm.

Citation Information

Patent Citations

  • Simple and convenient resorcinol formaldehyde resin hollow composite material and preparing method of derivative thereof

    CN105061705A